SLOVENIAN SPORT TOURISM DESTINATIONS AND THEIR COMPETITIVENESS - Maja Uran Maravić; Jakob Bednarik; Miha Lesjak (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
This paper assesses the competitiveness of Slovenian sport tourism destinations and compares it with other domestic destinations and those abroad. The methodology is based on different destination competitiveness models. An integrated instrument of the sport destination competitiveness was developed and tested for validity of content and used to assess the competitiveness. There are eight main hypotheses tested. The research results confirm the main hypothesis − that Slovenian tourism managers believe Slovenian destinations are more competitive at home than abroad. The contribution of the research lies in the fact that it has applied the generic instrument for measuring destination competitiveness on sport tourism destinations and, for the first time, their competitiveness is measured in Slovenia.